Student's worksheet with guided inquiry approach on sub materials of endocrine system enriched with reducing process of diabetic blood sugar levels - Endah Maulina; Titin Titin; Wolly Candramila (Universitas PGRI Semarang, 2022)
The use of student’s worksheets as teaching materials and supporting learning activities is still not evenly distributed. The components are sometimes incomplete. This study aims to describe the development and determine the feasibility of guided inquiry-based worksheets as teaching materials for the endocrine system sub material for second-grade of high schools. This study used a 4D development model limited to three defining, designing, and developing stages. The student’s worksheets were designed based on the problems obtained from interviews with biology teachers in three different schools. At the development stage, the worksheets were validated by five validators consisting of two lecturers and three biology teachers in Pontianak. The validation assessment contained four aspects: the feasibility of the content/material, language, presentation, and graphics with 19 criteria. The student’s worksheet was successfully developed with enrichment in the form of discourse analysis activities related to diabetes and the process of lowering blood sugar levels by plant extracts with guided inquiry stages. The feasibility analysis results of the guided inquiry-based student’s worksheet obtained CVR and CVI values of 1 each so that product can be declared ready for the limited and extensive trial phase. However, the significance of the enrichment topics in this student’s worksheet still needs to be re-examined directly in the teaching and learning process in the Endocrine System Sub material for second grade of high school in both small and large scales groups.